Perceraian (Kajian Sosiologis terhadap Kasus-kasus pada Pengadilan Agama Banda Aceh) - Mukhlis Azis (Universitas Islam Negeri Ar-Raniry, 2001)
Divorce, which is a lawful (halal) but detested (makruh) act in Islam, is a common phenomenon in society. Usually, it is the husband who takes initiative to the case, not the other way around. Yet, with the recently growing number of divorce cases, the percentage of divorce initiated by the wife has significantly increased. This phenomenon is no doubt an urgent topic to be studied.